The use of western standardized psychological tests in non-western contexts - Marshall, Dylan D. (Animo Repository, 2013)
The aim of this literature review is to examine the issues related to the use of standardized psychological tests developed in the West within non-Western contexts. The central thesis is that it is vital to be aware of the cultural differences and how these may affect performance on standardized psychological tests. Psychologists must be aware of this when they are assessing and evaluating students in schools in non-Western cultures. The review first presents a theoretical framework for understanding cultural differences in psychology. It then reviews researches that highlight the methodological and ethical controversies related to the use of standardized tests within non-Western contexts. The review then examines the steps that can be put in place to ensure equivalence when using standardized tests outside of the context that they were developed. This paper concludes by arguing that culturally relevant tests should be developed in a local context.